The influence of travel motivations and islamic religiosity on islamic travel preference : a comparison between Muslim Malaysian and Iranian University student / Ali Hemati - Hemati, Ali (2012)
Islamic Tourism in the Muslim Societies which has a fast growth in tourism industry attracts the attention of many researchers for academic purpose and also catches the attention of for the business purposes. Present study attempts to examine the relationship between three motivational factors namely “Generic”, “Islamic”, “Hedonistic” to Islamic Travel Preference. This research compares the similarity and differences between Malaysians and Iranians in terms of Islamic travel preferences, travel motivations, and Islamic religiosity; and also evaluate the importance level of Islamic religiosity on the relationship between travel motivations and Islamic travel preference. This study is a quantitative research which its sample population were conveniently selected from Muslim Malaysian and Iranian University Students. In addition, linear regression analysis and independent groups t-test techniques have been utilized for data analysis. The findings indicate that generic motivational factors do not significantly contribute to predict any preferences in an Islamic travel. Besides, Islamic motivational factors positively contribute to predict any preferences in an Islamic travel while hedonistic motivational factors significantly have a negative contribute in predicting Islamic travel preferences. On the other hand the findings reveal that, Islamic religiosity increases the strength of relationship between Islamic and hedonistic motivational factors and Islamic travel. Furthermore, this study shows that there is a significant difference between Malaysian Muslim university students and Iranian university students in terms of Islamic travel preferences, travel motivations and the level of religiosity, even though both group tend to have similar attitudes and preferences in this study.